2021
DOI: 10.3389/fmicb.2021.716393
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tet(X4) in Escherichia coli From Duck Farms in Southeast China

Abstract: ObjectivesCarbapenems, colistin, and tigecycline are critically important antibiotics in clinics. After the global appearance of blaNDM and mcr mediating the resistance to carbapenems and colistin, respectively, tigecycline becomes the last-resort drug against severe human infections caused by multidrug-resistant bacteria. Recently, a mobile tigecycline resistance gene tet(X4) has been identified in Escherichia coli, Klebsiella pneumoniae, and Acinetobacter baumannii that causes high resistance to tigecycline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…Interestingly, we found that the carriage of tet (X4)-positive plasmids encoding H-NS had low fitness cost in E. coli TOP10 and K. pneumoniae ATCC700603, rather than in S. Enteritidis ATCC13076. These findings support the fact that tet (X4) was reported in E. coli and K. pneumoniae , but not in S. Enteritidis ( He et al, 2019 ; Yu et al, 2021 ), suggesting that the tet (X4)-carrying plasmids impose a high cost in Salmonella . It would be interesting to investigate the underlying mechanisms behind this phenomenon.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, we found that the carriage of tet (X4)-positive plasmids encoding H-NS had low fitness cost in E. coli TOP10 and K. pneumoniae ATCC700603, rather than in S. Enteritidis ATCC13076. These findings support the fact that tet (X4) was reported in E. coli and K. pneumoniae , but not in S. Enteritidis ( He et al, 2019 ; Yu et al, 2021 ), suggesting that the tet (X4)-carrying plasmids impose a high cost in Salmonella . It would be interesting to investigate the underlying mechanisms behind this phenomenon.…”
Section: Discussionsupporting
confidence: 87%
“…Ecological niches in which plasmid-encoded TIG resistance tet (X) genes have been detected are shown in Table 1 . Clearly, there is increasing evidence of plasmid-encoded TIG resistance tet (X) genes reported in countries across Europe, Asia, United States, South America, and Africa involving humans, food animals, including chickens, pigs, ducks, pigeons, geese, and cattle, as well as companion animals, food animal products (meats), aquaculture and environment such as soil, livestock-farm water, wastewaters, sewages, and wildlife as reservoirs of MTR ( Bai et al, 2019 ; Chen et al, 2019a , b , 2020 , 2021 ; He et al, 2019 ; Sun C. et al, 2019 , 2020 ; Sun J. et al, 2019 ; Cao et al, 2020 ; Cui et al, 2020 , 2021b ; Ding et al, 2020 ; Du et al, 2020 ; He T. et al, 2020 ; Li et al, 2020 , 2021f ; Ma et al, 2020 ; Pan et al, 2020 ; Ruan et al, 2020 ; Song et al, 2020 ; Wang et al, 2020a , b ; Zhang et al, 2020b , 2021 ; Zheng et al, 2020 ; Cheng et al, 2021a , b ; Feng et al, 2021 ; Hirabayashi et al, 2021a , b ; Hsieh et al, 2021 ; Li et al, 2021e , f ; Lu et al, 2021 ; Marathe et al, 2021 ; Martelli et al, 2021 ; Mohsin et al, 2021 ; Soliman et al, 2021 ; Sun et al, 2021a , b ; Tang et al, 2021 ; Wang et al, 2021f , g ; Xu et al, 2021 ; Yu Y. et al, 2021 ; Wu et al, 2022 ; Zhai et al, 2022 ). We further demonstrate this, through the specific reservoirs in which plasmid-borne transmissible tet (X) and tmexCD-toprJ genes have been detected as shown in Table 2 .…”
Section: Distribution Reservoirs and Traits Of Mobile Tigecycline Res...mentioning
confidence: 99%
“…Moreover, this situation can be exacerbated when an incriminated organism possesses an MTR mechanism [plasmid-encoded tet (X) or efflux pump] and gene coding resistance to other last-resort antimicrobials such as COL (conferred by mcr ), fluoroquinolones, extended-spectrum cephalosporins and fosfomycin. Regrettably, such superbugs have already been isolated from humans ( He et al, 2019 ; Ding et al, 2020 ; Ruan et al, 2020 ; Li et al, 2021a ), food animals ( He et al, 2019 ; Sun C. et al, 2019 ; He T. et al, 2020 ; Li et al, 2020 , 2021c ; Xu et al, 2021 , 2022 ; Yu Y. et al, 2021 ), meat ( Bai et al, 2019 ; Du et al, 2020 ; Mohsin et al, 2021 ; Soliman et al, 2021 ), and environment ( Chen et al, 2019a ; Cui et al, 2020 ; Mohsin et al, 2021 ; Yu Y. et al, 2021 ). Sadly, tet (X) even with genes coding resistance to other last-resort antibiotics, are horizontally/laterally transferred/acquired at a high frequency rate intra/inter-species/genus ( Chen et al, 2019a ; Sun C. et al, 2019 ; Cui et al, 2020 ; Ding et al, 2020 ; Du et al, 2020 ; Marathe et al, 2021 ; Soliman et al, 2021 ; Zhang et al, 2021 ).…”
Section: Distribution Reservoirs and Traits Of Mobile Tigecycline Res...mentioning
confidence: 99%
See 2 more Smart Citations